Prediksi Inflow Daerah Aliran Sungai Larona Dengan Model Seasonal Autoregressive Integrated Moving Average - Tukiyat, Tukiyat; Sutrisno, Sutrisno; Anggai, Sajarwo (Universitas Pamulang, 2023)
Larona Watershed (DAS) Inflow Prediction entering the reservoir has a very important role in managing the reservoir's water resources. Various approaches using mathematical models have been carried out, the results of which can be used as management tools to understand estimates and predictions of future inflow values, especially in the context of managing and planning water utilization for company needs at PT Vale Indonesia Tbk. The research aims to find a prediction model for the water inflow of the Towuti, Matano and Mahalona reservoirs. The research method uses a statistical approach using the SARIMA (Seasonal Autoregressive Integrated Moving Average) model. Research data, time series data, monthly inflow of the Larona watershed for January 2006 – December 2019. The research results showed that the best model was SARIMA (2,0,1)(0,1,1)12. The mathematical model prediction formulated is 4.786 + 1.459t-1 – 0.648t-2 – 0.714 e_(t-1). The model accuracy level was tested using the RMSE (Root Mean Squared Error) criteria of 0.767, MAE (Mean Absolute Error) level of 0.592, MAPE (Mean Absolute Percentage Error) of 14.58. To validate the predicted values, the F test, Siegel-Turkey, Bartlett, Levene was carried out at the α=5% level. The test results for the difference between actual and predicted values were concluded to accept the null hypothesis, which means that there is no significant difference between the actual data values and the predicted data values.